Clinical epidemiological characteristics of patients with burns before and during the covid 19 pandemic at the Instituto Nacional de Salud del Niño San borja - Vásquez Yap Sam, Aída (2023)
Objective: To compare the clinical-epidemiological characteristics of patients with burns before and during the COVID-19 pandemic treated at the “Instituto Nacional de Salud del Niño San Borja” . The study: Analytical, retrospective study. Patients treated at the INSNSB, during the periods from March to December 2019 and 2020. Data were collected from medical records. For statistical, the SPSS v25 program (95% CI) was used. Findings: 139 patients were analyzed in each period. 60.4% and 76.3% of patients came from Lima, before and during the pandemic, respectively; The most frequent level of education of the responsible family member was high school (42.3% and 58.2%). Also, minor burns showed an increase before and during the pandemic (49.9% and 61%). Conclusions: Significant changes were observed in the origin, degree of the responsible family member and the severity of burn between both periods.